PENGEMBANGAN SISTEM PENYEWAAN PERLENGKAPAN CATERING PADA CV. ROESMORA SEHATI MANDIRI - Muhammad Rafi Herman; Riezca Talita Trista; Alexius Ulan Bani (Jurnal Sains dan Teknologi Widyaloka (JSTekWid), 2023)
The development of a catering equipment rental system at CV. Roesmora Sehat Mandiri aims to improve the efficiency of managing catering equipment rentals, which were previously done manually. The developed system allows for more accurate and structured recording, borrowing, and returning of equipment, reducing human errors and increasing transaction transparency. With the application of information technology, CV. Roesmora Sehat Mandiri can monitor stock in real-time and manage customer data and transactions more easily. The implementation of QR code technology in the inventory system also enhances the efficiency of recording and tracking items. This system development is expected to improve service quality, customer satisfaction, and become a model for the catering industry to enhance business competitiveness.